Photosynthetic Picoeukaryotes Diversity in the Underlying Ice Waters of the White Sea, Russia - Tatiana A. Belevich; Ludmila V. Ilyash; Irina A. Milyutina; Maria D. Logacheva; Aleksey V. Troitsky (Diversity, 2020)
The White Sea is a unique basin combining features of temperate and arctic seas. The current state of its biocenoses can serve as a reference point in assessing the expected desalination of the ocean as a result of climate change. A metagenomic study of under-ice ice photosynthetic picoeukaryotes (PPEs) was undertaken by Illumina high-throughput sequencing of the 18S rDNA V4 region from probes collected in March 2013 and 2014. The PPE biomass in samples was 0.03–0.17 µg C·L−1 and their abundance varied from 10 cells·mL−1 to 140 cells·mL−1. There were representatives of 16 algae genera from seven classes and three supergroups, but Chlorophyta, especially Mamiellophyceae, dominated. The most represented genera were Micromonas and Mantoniella. For the first time, the predominance of Mantoniella (in four samples) and Bolidophyceae (in one sample) was observed in under-ice water. It can be assumed that a change in environmental conditions will lead to a considerable change in the structure of arctic PPE communities.